THE CATHOLICOSATE OF THE GREAT HOUSE OF CILICIA AND THE EMIGRATION OF ARMENIANS FROM THE SANJAK OF ALEXANDRETTA - Hovhannisyan, Edgar (Armenian Folia Anglistika, 2025)
Following the Genocide of 1939, Armenians saw the biggest emigration from the Sanjak of Alexandretta. Over 30.000 displaced emigrants settled mostly in the territory of Syria and Lebanon. This process was predominantly regulated by the Catholicosate of Cilicia. The article highlights the organization of the emigration of the Armenians of the Sanjak and the role of the Catholicosate of Cilicia in this work.